PENGARUH PERTUMBUHAN GULMA KROKOT, Portulaca oleracea, TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH Allium ascalonicum 'TOPO' - Fitriani Soamole; Zauzah Abdullatif; Hayun Abdullah (Scripta Biologica, 2018)
The purpose of this study to determine the effect of the Portulaca oleracea purslane growth time on the growing and production of Topo local cultivar of red onions Allium ascalonicum which is originally from Tidore island. We used Randomized Block Design (RBD) to run six treatments in three blocks which consisted of P0 (without purslane weed as the control), P1 (purslane growth in the beginning of onion planting), P2 (growing of purslane after 10 days planting of onion), P3 (growing of purslane after 20 days planting of onion), P4 (growing of purslane after 30 days planting of onion), and P5 (growing of purslane after 40 days planting of onion), so there were 18 experimental units. Then, data were analysed by ANOVA, if there any significant effect which was continued by Least Significance Different test (ɑ=0,05). The results showed that the longer purslane weeds associated with Topo red onion could suppress the growth of this red onion and finally decrease the production. Finally, we found that production of P2 (103.33 g/plot) as the lowest production, which differed significantly with P0 (483.33 g/plot). Therefore, we suggested if weed control of purslane could be done at the age seven until forty days after planting and this information could be used as an essential strategy to controlling purslane weed.